ChemInform Abstract: Catalytic Suzuki Couplings by an Amido Pincer Complex of Palladium. Issue 25 (June 2016) - Liang, Lan‐Chang; Chien, Pin‐Shu; Song, Liang‐Hua
Abstract: Noteworthy, the catalysis succeeds in the high yield production of sterically encumbered tri‐ortho‐substituted biaryls (VI).